IMOM Al-BUXORIY ASARLARIDA MA’NAVIY-AXLOQIY TARBIYA - Norboyeva, S.M. (SCIENCE and SOCIETY, 2024)
The article presents scientific considerations on the use of the works of Imam al-Bukhari for the development of the basic spiritual competencies of future pedagogues.